Class I and Class II Patients Treated with Damon System: A Study of Transversal, Sagittal and Torque Values Variations - Francesca Cremonini; Daniela Guiducci; Emanuela Pierotti (Association of Support to Oral Health Research (APESB), 2023)
Objective: To analyze the transversal and anterior-posterior changes obtained in patients treated only with the Damon system. Material and Methods: 51 patients with either class I or class II division 1 sagittal relationship treated with the Damon system and the same archwire sequence were retrospectively selected. Dental casts of each patient before (T0) and after treatment (T1) were scanned and analyzed using NEMOCAST 3D software. Inter-molar, inter first-premolar, inter-second premolar and inter-canine distances were measured in both upper and lower arches. Initial and final lateral cephalograms were traced using the OrisCeph program. Pre and post-treatment measurements were compared using the t-test for repeated measurements. The Pearson Correlation Index and Linear Regression Analysis were used to determine the dependence between continuous variables. The significance level was set at 0.05. Results: Transversal diameters in the upper arch increase statistically significantly, especially in the bicuspid area. Initial intra-arch diameter was the only statistically significant variable correlated with the final expansion obtained. A linear negative correlation between the initial latero-posterior torque and the final expansion was observed in both arches. Conclusion: Using identical arches in patients with very different initial characteristics, the changes in bicuspids' diameters remain the most predominant. Patients with initial more negative torque in the posterior region had a higher expansion amount.